2022
DOI: 10.31557/apjcp.2022.23.3.867
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Inhibits Viability and Migration of MCF7 Breast Cancer Cells

Abstract: Objective: Atorvastatin is commonly used as a lipid lowering drug. The emerging interest in statins as anticancer agents is based on their pleiotropic effects on cancer cells. Among the statins, atorvastatin, and in cancers, breast malignancies have received less attention in preclinical investigations. In order to enhance the efficacy of cancer treatment, adjuvant, less expensive therapeutic strategies have been recently noticed. In this case, we investigated the in-vitro effect of atorvastatin o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The in vitro cytotoxicity study for both Lf decorated and undecorated ATR Ca-SLNs was carried out on MCF-7 cells ( Abolghasemi et al, 2022 ; Gambhire et al, 2018 ) for 24 h to study the antitumor effect of ATR Ca as well as the potential of Lf as a targeting ligand on cell viability. Despite the well-established understanding that statins exhibit their anticancer effects in laboratory settings along the epithelial-mesenchymal axis, where mesenchymal cells have greater sensitivity to statins compared to epithelial or hybrid epithelial-mesenchymal tumor cells, ( van Leeuwen et al, 2022 ; Warita et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The in vitro cytotoxicity study for both Lf decorated and undecorated ATR Ca-SLNs was carried out on MCF-7 cells ( Abolghasemi et al, 2022 ; Gambhire et al, 2018 ) for 24 h to study the antitumor effect of ATR Ca as well as the potential of Lf as a targeting ligand on cell viability. Despite the well-established understanding that statins exhibit their anticancer effects in laboratory settings along the epithelial-mesenchymal axis, where mesenchymal cells have greater sensitivity to statins compared to epithelial or hybrid epithelial-mesenchymal tumor cells, ( van Leeuwen et al, 2022 ; Warita et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…The selection for the MCF7 cell line was based on their classification as a luminal A breast cancer cell line ( Moon et al, 2020 ) which is considered the most common breast cancer molecular subtype in Egypt accounting for >42% of total breast cancer cases ( El-Hawary et al, 2012 ). Added to that, there have been previous studies in the literature that have demonstrated the antitumor effect of ATR against breast cancer using MCF7 cell lines ( Abolghasemi et al, 2022 ; Gambhire et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…As hyperlipidemia increases the risk of CRC, ATO lowers lipid concentration through complete inhibition of 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase [8]. Moreover, this compound can also inhibit cancer cell proliferation, migration, and survival [9,10]. The reason for ATO interaction with other drugs also lies in its complex metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…As a lipid-lowering drug, Atorvastatin is widely used in clinical practice to lower cholesterol and reduce the occurrence of cardiovascular events [9,10] . In recent years, studies have shown that Atorvastatin have good anti-tumor effects in breast cancer, leukemia, liver cancer, thyroid cancer, prostate cancer and other tumors [11][12][13][14][15][16][17] . The antitumor mechanism of atorvastatin may induce malignant apoptosis and cell cycle, autophagy, and cellular stress, and reduce cell migration, thereby affecting cell proliferation and migration.…”
Section: Introductionmentioning
confidence: 99%